(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
The aim of this study was to determine the effect of a teaching procedure of constructed response matching to sample (CRMTS) on learning monetary relations. Six deaf children divided into two groups. They were taught via CRMTS about values in Brazilian Sign Language (LIBRAS) and their relations to prices and pictures of coins, followed by testing in symmetrical relations (BA and CA) and tests between prices and pictures of coins (BC), the inverse (CB), facsimile of Brazilian real bills and prices (DB), between pictures of coins (CC) and pictures of facsimile of Brazilian real bills (DD). In tests, in both groups, there was the emergence of conditional relations between prices and monetary values in LIBRAS and between pictures of coins and monetary values in LIBRAS. This indicates that, regardless of the initial repertoire of the participants were learning about this type of conditional monetary. In tests there was variability in responses what may have occurred because of these relations involve greater complexity.